Respiratory Mechanics and Outcomes in Immunocompromised Patients With ARDS: A Secondary Analysis of the EFRAIM Study - Demoule, Alexandre; Antonelli, Massimo; Schellongowski, Peter; Pickkers, Peter; Soares, Marcio; Meyhoff, Tine; Rello, Jordi; Bauer, Philippe R; van de Louw, Andry; Lemiale, Virgine; Grimaldi, David; Martin-Loeches, Ignacio; et al. (Chest, 2020)
BACKGROUND: In view of the high mortality rate of immunocompromised patients with ARDS, it is important to identify targets for improvement. RESEARCH QUESTION: This study investigated factors associated with mortality in this specific ARDS population, including factors related to respiratory mechanics (plateau pressure [Pplat,rs], compliance [Crs], and driving pressure [ΔPrs]). STUDY DESIGN AND METHODS: This study consisted of a predefined secondary analysis of the EFRAIM data. Overall, 789 of 1,611 patients met the Berlin criteria for ARDS, and Pplat,rs, ΔPrs, and Crs were available for 494 patients. A hierarchical model was used to assess factors at ARDS onset independently associated with hospital mortality. RESULTS: Hospital mortality was 56.3%. After adjustment, variables independently associated with hospital mortality included ARDS of undetermined etiology (OR, 1.66; 95% CI, 1.01-2.72), need for vasopressors (OR, 1.91; 95% CI, 1.27-2.88), and need for renal replacement therapy (OR, 2.02; 95% CI, 1.37-2.97). ARDS severity according to the Berlin definition, neutropenia on admission, and the type of underlying disease were not significantly associated with mortality. Before adjustment, higher Pplat,rs, higher ΔPrs, and lower Crs were associated with higher mortality. Addition of each of these individual variables to the final hierarchical model revealed a significant association with mortality: ΔPrs (OR, 1.08; 95% CI, 1.05-1.12), Pplat,rs (OR, 1.07; 95% CI, 1.04-1.11), and Crs (OR, 0.97; 95% CI, 0.95-0.98). Tidal volume was not associated with mortality. INTERPRETATION: In immunocompromised patients with ARDS, respiratory mechanics provide additional prognostic information to predictors of hospital mortality. Studies designed to define lung-protective ventilation guided by these physiological variables may be warranted in this specific population.
Keywords: mechanika dýchání; syndrom dechové tísně; Male; dechový objem; Respiratory Mechanics; následné studie; prognóza; ventilace umělá s výdechovým přetlakem; Aged; Prospective Studies; mužské pohlaví; senioři; Tidal Volume; Follow-Up Studies; Immunocompromised Host; Positive-Pressure Respiration; lidé; ženské pohlaví; imunokompromitovaný pacient; Humans; Respiratory Distress Syndrome; Prognosis; Female; lidé středního věku; Middle Aged; prospektivní studie